Taxonomic applications of the esophageal flapper valve in Bairdoppilata and Glyptobairdia (Bairdiidae, Ostracoda), with comments on anatomy, ontogeny, and geography - Maddocks, Rosalie F. (Zootaxa, 2022)
The esophageal valve follows a uniform design in species of Bairdoppilata and Glyptobairdia, having a thin, wedge-shaped plate with 10–16 small teeth along the posterior edge. This structure may be added to the list of diagnostic anatomical traits, including the scissors-like antennal claws and complex distal appendages of the hemipenis, for identification of living species of these genera. These soft anatomical characters are invariably associated with bairdoppilatan supplemental dentition on the carapace, which supports the reliability of that trait for identification of fossils. This report evaluates the consistency of the esophageal plate in nine living species of Bairdoppilata. Photographs of the Oligocene type species, B. martyni, are provided for the first time. Geographic populations of the common Caribbean species, B. cushmani, display some heterogeneity in carapace size and proportions. B. hirsutella, n. sp., is proposed for a population previously misidentified as B. hirsuta. Supplemental information and illustrations are provided for Glyptobairdia coronata and G. trinodosa.